An objective structured teaching exercise for faculty training and assessment of teaching ability in interprofessional collaborative practice and education - Hsiu-Chen Yeh; Sin-Yi Huang; Tsung-Ying Chen; Ming-Chen Hsieh (Tzu Chi Medical Journal)
Objective: Improving clinical teachers' ability to teach interprofessional collaborative practice warrants development in current faculty training programs; in particular, current education training emphasizes experiential learning and multiple teaching strategies. The purpose of this study was to establish a teaching model to apply interdisciplinary collaborative care and to improve clinical teachers' execution of interprofessional practices. Materials and Methods: Health-care faculty members were studied; this study assessed a teacher education curriculum for interprofessional education (IPE) and applied an objective structured teaching exercise (OSTE) to evaluate IPE execution by clinical teachers. Results: The OSTE improved clinical teachers' IPE execution, verifying the necessity for multistrategy teaching in faculty training programs. Conclusions: This study provides different types of interprofessional faculty training and assessments. Development of an OSTE requires long-term planning, and IPE should also be incorporated into formal programs.